Biological research of Grabia River - fifty years of activity - Siciński, Jacek; Tończyk, Grzegorz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2005)
Grabia, a small still close to natural conditions lowland river, has been an object of special interest for Łódź hydrobiologists for more than 50 years. Over 100 scientific papers and over 100 master theses were produced in the Faculty of Biology and Environmental Protection University of Łódź. The initiator was Prof.L.K. Pawłowski who spent many years conducting research into the river. The ground and the first research objective was to recognize the fauna diversity. The checklist encompass almost 1000 invertebrate and 24 fish species. Taxonomy, biology and ecology of various taxa have made for many decades an essential trend of scientific activity. Special attention was dedicated to rotifers, leeches, branchiobdellids, snails and bivalves, gammarids and copepods as well as aquatic insects, fish and also diatoms. Some aspects of zoobenthos and Zooplankton communities ecology was the subject of 13 Ph.D.theses. The river with its rich animal and plant communities was also the subject of dynamics of river ecosystem research. The study on the structure of invertebrate assemblages on the background of habitat diversity has been recently conducted. The model may be treealed as a reference to the restoration of Europaean rivers and their valleys.